Pharmacokinetics of aspirin and salicylate in relation to inhibition of arachidonate cyclooxygenase and antiinflammatory activity. - Higgs, G A (1987)
Among the nonsteroid antiinflammatory drugs there is generally a close correlation between the potency of their inhibition of arachidonate cyclooxygenase, and thus prostaglandin production, and their antiinflammatory activity. One anomaly in this generalization is that whereas aspirin and salicylate are equipotent as antiinflammatory agents, salicylate is less active than aspirin in inhibiting prostaglandin production in vitro. Using rats, we have now measured the concentrations of aspirin and salicylate in plasma and in inflammatory exudates after their oral administration and determined their effects on thromboxane B2 production in clotting blood and prostaglandin (PG) E2 concentrations in the exudates. We have also investigated the effects of both drugs, at concentrations achieved in the exudates, on PGE2 production by nonproliferative explants of acutely inflamed tissues. Aspirin is rapidly metabolized, resulting in peak concentrations of salicylate in the plasma and exudate that exceeded peak concentrations of aspirin by 30- to 50-fold. Furthermore, concentrations of aspirin rapidly declined, whereas high concentrations of salicylate persisted in the plasma and in the exudate for up to 6 hr after a single administration of aspirin. Both drugs reduced PGE2 concentrations in inflammatory exudates by 50-70%, but aspirin was considerably more potent than salicylate in inhibiting thromboxane B2 production in clotting blood. The concentration of salicylate found in inflammatory exudates 6 hr after the administration of aspirin was sufficient to reduce PGE2 production in explants by more than 50%. We conclude that the antiinflammatory action of both drugs depends on the inhibition of PGE2 synthesis by salicylate.